OER by Discipline Guide: University of Ottawa (Version 2.0 - June 2022) - Brunet, Mélanie; Lachaîne, Catherine (Université d'Ottawa | University of Ottawa, 2022)
The OER by Discipline Guide is a tool suggesting open educational resources for courses at the University of Ottawa. uOttawa. Its purpose is to help professors get acquainted with existing OER in their disciplines and facilitate their use. This version supersedes Version 1.0 – June 2021. Consult the online (webbook) version of this guide for the latest updates.
Keywords: Open educational resources (OER); Affordable course materials